Program Management Meeting in Burkina Faso - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
During October 2012, the Independent Science Panel (ISP) and Program Management Committee (PMC) met for a week long conference. During the meeting a field trip to one of benchmark sites of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) was conducted. The trip showed how farmers have changed farming practices and what conditions they are working under. Photo: M.Tall (CCAFS West Africa).